Analyzing the Impact of Digital Transformation in Islamic Philanthropy using UTAUT Model - Mukhamad Yazid Afandi (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to assess individual habits in adopting digital payment technologies in Islamic philanthropic institutions. This research uses the UTAUT model, which explains user behavior in relation to information technology adoption. The population of this study was people who have used digital payments in philanthropic institutions, e.g., M-banking, QRIS, e-wallet, e-money, crowdfunding, marketplace, etc. A sample of 250 respondents was obtained using a random sampling technique. The UTAUT model was performed using structural equation modeling (SEM) via SmartPLS. The results showed that all constructs had a significant positive impact, except for the effect of facilitating conditions on usage behavior. This study shows that the digitization of payment transactions is still aimed at the segment of well-informed technology users. Policyholders, therefore, need to become more involved in the digital transformation campaign, which targets all potential segments, e.g., the middle-aged working class. Due to this segmentation, they have a high awareness of donations in addition to the income opportunities.